In vitro bacterial adherence on teeth submitted to whitening with Musa paradisiaca - Úrsula Pantigozo-Morán; José González-Cabeza; María Espinoza-Salcedo (Universidad de Concepción., 2022)
Objetive: To compare in vitro bacterial adherence on teeth submitted to whitening with 50% ethanolic extract of Musa paradisiaca and 35% hydrogen peroxide. Material and Methods: The study was experimental and used 18 premolars that were grouped into: G1 (control), G2 (50% ethanol extract of Musa paradisiaca) and G3 (35% hydrogen peroxide). The teeth were then exposed to a Streptococcus mutans culture for 24 hours, followed by centrifugation in thioglycolate broth. A culture on trypticase soy agar was done with a 1 in 100 dilution, and after 48 hours colony forming units (CFU) were counted. Statistical analysis was performed using the ANOVA test, complemented by the Bonferroni post-hoc. Results: Bacterial adherence was 77x105 CFU/ml in Group 3 using 35% hydrogen peroxide, 40x105 CFU/ml in Group 2 using 50% ethanol extract of Musa paradisiaca, and 89x104 CFU/ml in Group 1 (control). The difference between the three groups was significant (p=0.000). Conclusion: Both whitening methods cause bacterial adherence to the tooth surface, although to a lower degree with Musa paradisiaca.eses.